A novel high performance configuration of electrochemical cell to produce alkali for sequestration of carbon dioxide. (20th November 2016) - Mehmood, Asad; Iqbal, Muhammad Ibrahim; Lee, Ju-Young; Hwang, Jinyeon; Jung, Kwang-Deog; Ha, Heung Yong
Graphical abstract: Highlights: A novel configuration of electrochemical cell is proposed for production of alkali. New configuration consists of two cation exchange membranes (a CEM-CEM system). New membrane configuration eliminates issues related to anion exchange membrane. Optimized CEM-CEM system shows a remarkable improvement of output current density. An energy saving upto 740 kWh ton −1 for mineralization of CO2 is achieved. Abstract: We propose a new configuration of a 3-compartment electrochemical cell for producing alkali that is subsequently utilized for mineralization of carbon dioxide. In this new membrane configuration, a second cation exchange membrane (CEM) replaces the anion exchange membrane (AEM) employed in a standard cell configuration. The electrochemical cell comprising of two cation exchange membranes (a CEM-CEM system) eliminates the issues associated with the AEM such as low ionic conductivity and inferior mechanical strength. All of tested CEM-CEM combinations exhibit superior electrochemical performance with considerable reduction of energy requirement for NaOH production in comparison to the standard AEM-CEM configuration. The optimized two-CEMs-based system presents a remarkable enhancement of output current density by 2.5-fold and a substantial input energy savings up to 740 kWh ton −1 for mineralization of carbon dioxide to produce sodium carbonate.